Determination of an ion exchange constant by the use of a kinetic probe: a new semiempirical kinetic approach involving the effects of 3-f- and 4-f-substituted benzoates on the rate of piperidinolysis of anionic phenyl salicylate in aqueous cationic micelles - Yusof, N.S.M.; Khan, M.N. (American Chemical Society, 2010)
Pseudo-first-order rate constants (k(obs)) for the nucleophilic substitution reaction of piperidine (Pip) with ionized phenyl salicylate (PS(-)), obtained at a constant [PIP](T) (= 0.1 M), [PS(-)](T)( = 2 x 10(-4) M), [CTABr](T) (cetyltrimethylammonium bromide), <= 0.06 M NaOH, and a varying concentration of.MX ( = 3-FC(6)H(4)CO(2)Na, 3-FBzNa and 4-FC(6)H(4)CO(2)Na, 4-FBzNa), follow the kinetic relationship k(obs) = (k(0) + theta K(X/S)[MX])/(1+ K(X/S)[MX]) which is derived by the use of the pseudophase micellar (PM) model coupled with an empirical equation. The empirical equation explains the effects [MX] on CTABr micellar binding constant (K(s)) of PS(-) that occur through X(-)/PS(-) ion exchange. Empirical constants theta and K(X/S) give the parameters F(X/S) and K(X/S), respectively. The magnitude of F(X/S) gives the measure of the fraction of micellized PS(-) transferred to the aqueous phase by the limiting concentration of X(-) through X(-)/PS(-) ion exchange. The values of F(X/S) and K(X,S) have been used to determine the usual thermodynamic ion exchange constant (K(X)(Y)) for ion exchange process X(-)/Y(-) on the CTABr micellar surface. The values of K(X)(BR). (where Br = Y) have been calculated for X = 3-FBzNa and 4-FBzNa. The mean values of K(X)(Br) are 12.8 +/- 0.9 and 13.4 +/- 0.6 for X(-) = 3-FBz(-) and 4-FBz(-), respectively. Nearly 3-fold-larger values of K(X)(BR) for X = 3-FBz(-) and 4-FBz(-) than those for X = Bz(-), 2-ClBz-, 2-CH(3)Bz(-), and the 2,6-dichlorobenzoate ion (2,6-Cl(2)Bz(-)) are attributed to the presence of wormlike micelles in the presence of > 50 mM 3-FBz(-) and 4-FBz(-) in the [CTABr](T) range of 5-15 mM. Rheological properties such as shear thinning behavior of plots of shear viscosity versus the shear rate at a constant [3-FBz(-)] or [4-FBz(-)] as well as shear viscosity (at a constant shear rate) maxima as a function of the concentrations of 3-FBz(-) and 4-FBz(-) support the conclusion, derived from the values of K(X)(Br), for the probable presence of wormlike/viscoelastic micellar solutions under the conditions of the present study.